KRITIK MAHMUD SYALTUT TERHADAP PRAKTIK NIKAH MUT’AH SYI’AH - Ayu, Diyan Putri (Fakultas Syariah INSURI Ponorogo, 2019)
The purpose of this study is to describe the Mut'ah marriage criticism carried out by the Shiite group. This criticism was leveled by Mahmud Syaltut. The method used is descriptive-qualitative. The results of this study indicate that Mahmud Syaltut believes that Mut'ah's marriage is in contradiction with the purpose of marriage marriages, which is to form a family and offspring, whereas Mut'ah's marriage does not realize that goal. Mahmud Syaltut uses his ijtihad in solving this problem by combining Islamic sources, namely the Koran, Hadith and Istinbāṭ. According to Syaltut, the marriage prohibition of Mut'ah contains maslahah and avoids mafsadah.